A nation of speechifiers : making an American public after the Revolution - Eastman, Carolyn (University of Chicago Press, 2010)
In the decades after the American Revolution, inhabitants of the United States began to shape a new national identity. Telling the story of this messy yet formative process, Carolyn Eastman argues that ordinary men and women gave meaning to American nationhood and national belonging by first learning to imagine themselves as members of a shared public. She reveals that the creation of this American public--which only gradually developed nationalistic qualities--took place as men and women engaged with oratory and print media not only as readers and listeners but also as writers and speakers. Eas.